2021
DOI: 10.1371/journal.pone.0245054
|View full text |Cite
|
Sign up to set email alerts
|

Quality of oxytocin and misoprostol in health facilities of Rwanda

Abstract: Sustainable Development Goal 3.1 calls for a reduction of the maternal mortality ratio to less than 70 per 100,000 live births by 2030. The most important cause of maternal mortality is post-partum haemorrhage (PPH). Oxytocin injections and misoprostol tablets are medicines of first choice for the management of PPH in low- and middle-income countries (LMICs). Unfortunately, both substances are chemically unstable, and previous studies have revealed serious quality problems of these medicines in LMICs. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Despite the prevalent belief that misoprostol is a stable and reliable drug, several studies published over the last years raise concerns about the quality of this medicine 20 21 27 47 48. The recognition that misoprostol can have significant quality issues in LMICs was largely lacking until the publication of a systematic review by Torloni et al in 2020 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the prevalent belief that misoprostol is a stable and reliable drug, several studies published over the last years raise concerns about the quality of this medicine 20 21 27 47 48. The recognition that misoprostol can have significant quality issues in LMICs was largely lacking until the publication of a systematic review by Torloni et al in 2020 20.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their clinical importance in maternal health, the quality of oxytocin and misoprostol is substandard in many settings, especially in LMICs, mainly due to low content of active pharmaceutical ingredient 19–21. This may be due to production or packaging issues, or suboptimal storage conditions 22.…”
Section: Introductionmentioning
confidence: 99%
“…39 , 65 – 67 This allows stakeholders such as researchers to produce objective evidence that can inform regulatory decisions and protect public health, as illustrated in Malawi and Rwanda, where two extremely substandard brands of misoprostol tablets were found during a quality survey and led to the issuance of recalls by the regulatory authorities in the two countries and the WHO issued an alert to other countries. 68 , 69 Therefore, it is recommended that all alerts be uploaded to a publicly available database (e.g. ZAMRA website and Med Safety mobile app).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies revealed the low quality of oxytocin products in the Democratic Republic of the Congo (15 samples, 80% substandard), 9 Nigeria (159 samples, 74.2% failed), 10 and Nepal/Vietnam (42 samples, 31.0% failed) 11 . In contrast, there are also studies showing moderate and good quality oxytocin products 12–14 . For example, a study in Malawi and Ethiopia showed 89% and 96% of the samples, respectively, meeting the criteria 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…11 In contrast, there are also studies showing moderate and good quality oxytocin products. [12][13][14] For example, a study in Malawi and Ethiopia showed 89% and 96% of the samples, respectively, meeting the criteria. 13,14 A more recent systematic review by Torloni et al 15 found that, overall, around 40% of oxytocin samples were substandard.…”
Section: Introductionmentioning
confidence: 99%